A Study on Purchase Behavior of Rural Consumers of Jalandhar - Singh, Kanwal Gurleen; Nayyar, Varun; Dhillon, Ajwinder (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
In the past years, due to the lack of facilities available in the rural areas, the rural consumer headed towards nearby city to buy branded products and services. But today, the marketers have realized the potential in the rural market, which has become critical for them, be it for a branded shampoo or an automobile. Earlier, van campaigns, cinema commercials and a few wall paintings sufficed the purpose of the marketers to entice rural folks under their folds. But today, television has made the customer in a rural area quite literate about countless products that are on offer in the market place. The present study focuses on identifying the role of various advertisements in purchase of the product by rural consumer.